(untitled) (Journal of Ideas in Health, 2023)
Background: The growing body of evidence demonstrates both the desirable and undesirable consequences of organizational silence. This study aims to explore the influence of the organizational climate of silence on job performance through the mediating effects of work engagement (WE). Further, the degree to which supervisor support (SS) and work engagement moderate job performance are examined. Methods: A quantitative cross-sectional design was used for the study. Survey data from 14 hospitals and 15 health centers and community-based health planning services (CHPS) compounds in the Western Region of Ghana. We used the variable-to-sample ratio to determine an appropriate and sufficient sample size of 565 respondents. The hierarchical regression technique was employed in estimating the relationship between the variables. Results: In selecting an adequate and appropriate sample size for this current study, we relied on the variable-to-sample ratio. Results from the study showed that top management’s attitude to silence and the supervisor’s attitude to silence had a significant adverse effect on task performance (β=-.090, p< 0.05) and (β=-.110, p< 0.01). Work engagement had no role in mediating top managers’ and supervisors’ attitudes toward silence, communication opportunities, and task performance. Supervisor support acted as a moderating factor in the relationship between job engagement and task performance. In contrast, despite the direct positive relationship between supervisor support and contextual performance, it failed to moderate the relationship between work engagement and contextual performance. Conclusion: The study’s findings demonstrate the need for health managers and supervisors to become more conscious of silence. The results offer diverse recommendations for encouraging the sharing of relevant ideas, facts, and opinions within the health sector.